The Suitability of Tigris River Sediments from Tikrit, Northern Iraq, for Concrete Production and Road Construction Purposes - Khudhur, Mohanad Essa (Iraqi Journal of Science, 2021)
This study aims to assess the suitability of the sediments present in Tigris River, Tikrit city, northern Iraq for concrete production and road building purposes. Representative samples were collected from three selected stations at the study area using the channel modeling method. According to the grain size analysis, the sediments were classified as a type of poorly graded gravels (GP) depending on the unified soil classification system. The true specific gravity of the soil ranged between 2.28 and 2.568. The chemical analysis of the study samples revealed that gypsum content ranged between 0.82 and 1.69 %. Total soluble salts ranged 2.45- 3.87%, the organic matter content ranged 0.14- 0.76%, and the pH value was between 7.73 and 7.38%. The results of the Los Angeles Abrasion Test of selected samples showed weight loss ratios for the three stations (1, 2, and 3) of 19.9, 20.7, and 17.2%, respectively, while the maximum dry density values were 2.2739, 2.1940, and 2.2013 gm / cm3, respectively. The values ​​of the Californian Bearing Ratio test (C.B.R) were 53, 65 and 106 %, respectively. After comparing the results with the standard values of ASTM for concrete and roads materials, it was found that the samples were suitable for these purposes.